Systemic treatment approaches for sporadic desmoid-type fibromatosis: scarce evidence and recommendations - Kasper, Bernd (Oncology research and treatment, 2015)
Desmoid-type fibromatosis (DF) is a rare disease characterized by a monoclonal, fibroblastic proliferation and a variable and often unpredictable clinical course. Although histologically benign, DF is locally invasive and associated with a high local recurrence rate, but lacks any metastatic potential. As there is no established or evidence-based treatment approach available as of today, an individualized treatment strategy is fundamental in the light of highly variable clinical presentations, anatomic locations, and biological behaviors. Surgery with negative margins has been the cornerstone of DF treatment; however, an overall reassessment of the management of DF patients has taken place in the last few years, and preservation of function and quality of life has become a priority in these patients. Evidence is scarce for systemic treatment; different pharmacological options can be proposed and will be reviewed here. To better define possible therapeutic strategies, a consensus approach has been initiated, bringing together sarcoma experts from the European Organisation for Research and Treatment of Cancer (EORTC) Soft Tissue and Bone Sarcoma Group (STBSG) with patient advocates from Sarcoma Patients EuroNet (SPAEN). As a prerequisite, patients should be discussed in a multidisciplinary setting in centers/networks with specific expertise and experience in this disease.